Evaluating the morphology of the left atrial appendage by a transesophageal echocardiographic 3-dimensional printed model. Issue 38 (September 2017) - Song, Hongning; Zhou, Qing; Zhang, Lan; Deng, Qing; Wang, Yijia; Hu, Bo; Tan, Tuantuan; Chen, Jinling; Pan, Yiteng; He, Fazhi
Abstract : Abstract: The novel 3-dimensional printing (3DP) technique has shown its ability to assist personalized cardiac intervention therapy. This study aimed to determine the feasibility of 3D-printed left atrial appendage (LAA) models based on 3D transesophageal echocardiography (3D TEE) data and their application value in treating LAA occlusions. Eighteen patients with transcatheter LAA occlusion, and preprocedure 3D TEE and cardiac computed tomography were enrolled. 3D TEE volumetric data of the LAA were acquired and postprocessed for 3DP. Two types of 3D models of the LAA (ie, hard chamber model and flexible wall model) were printed by a 3D printer. The morphological classification and lobe identification of the LAA were assessed by the 3D chamber model, and LAA dimensions were measured via the 3D wall model. Additionally, a simulation operative rehearsal was performed on the 3D models in cases of challenging LAA morphology for the purpose of understanding the interactions between the device and the model. Three-dimensional TEE volumetric data of the LAA were successfully reprocessed and printed as 3D LAA chamber models and 3D LAA wall models in all patients. The consistency of the morphological classifications of the LAA based on 3D models and cardiac computed tomography was 0.92 ( P  < .01). The differences between the LAA ostium dimensions and depth measured using the 3D models were not significant from those measured on 3D TEE ( P  > .05). A simulation occlusion was successfully performed on the 3D model of the 2 challenging cases and compared with the real procedure. The echocardiographic 3DP technique is feasible and accurate in reflecting the spatial morphology of the LAA, which may be promising for the personalized planning of transcatheter LAA occlusion.